HUBUNGAN ANTARA PERSEPSI TERHADAP ATURAN KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN JOB INSECURITY PADA KARYAWAN BAGIAN OPERASIONAL PT. JATI LUHUR AGUNG SEMARANG - Wafika Chairunisa; Endah Mujiasih; Unika Prihatsanti (Faculty of Psychology, Diponegoro University, 2013)
Job insecurity is a feeling of helplessness to maintain desired continuity in a threatened job conditions. Conditions of job insecurity will have implications on the consideration of the employee to survive or not survive in the company. Job insecurity is influenced by employee perceptions of workplace safety and health regulations, the employee view of what the company aims to be maintained and guaranteed employee safety and health work. This study aimed to determine the relationship between perceptions of health and safety rules (K3) with job insecurity on employees at the operational part of PT. Jati Luhur Agung Semarang.The population in this study were employees at the operational part of PT. Jati Luhur Agung Semarang. Study sample totaled 65 people, achieved through proportional sampling technique. Data collection tool in this study is Scale Perceptions of Occupational Health and Safety Rules (33 aitem a = 0.919) and Job Insecurity Scale (25 aitem a = 0.892), which has been tested on 44 employees at the operational part of PT. Jati Luhur Agung Semarang.Simple regression analysis showed a correlation value -0.468 and p = 0.000 (p <0.05), ie, there is a negative and significant relationship between perceptions of the rules of Occupational Health and Safety with job insecurity. The more positive employee perceptions of the rules of Occupational Health and Safety (K3), the level of job insecurity experienced by employees is low, otherwise the negative employee perceptions of the rules of Occupational Health and Safety (K3), the level of job insecurity experienced by employees is high. Effective contribution of perceptions of the rules of Occupational Health and Safety (K3) with job insecurity by 21.9%. These results indicate that there are other factors at 78.1% which is not revealed in this study.